The Scholarship of Teaching and Learning: Transformation and Transgression - Laura Bolf-Beliveau (Park University, 2013)
Chapter Five of The Scholarship of Teaching and Learning Reconsidered (2011) suggests that traditional research scholarship methodology can inform and reform the ways in which we value and evaluate teaching. The authors discuss applying research methodology as way to complete this process. This article suggests that using theoretical frames, often used in qualitative methodology, creates another way to transform perceptions of the scholarship of teaching and learning. Two theoretical frames, transformative learning and critical consciousness, are explored and applied to the author's own teaching experiences and discipline mandates.